2021
DOI: 10.3389/fgene.2021.643304
|View full text |Cite
|
Sign up to set email alerts
|

Employees’ Views and Ethical, Legal, and Social Implications Assessment of Voluntary Workplace Genomic Testing

Abstract: Employers have begun to offer voluntary workplace genomic testing (wGT) as part of employee wellness benefit programs, but few empirical studies have examined the ethical, legal, and social implications (ELSI) of wGT. To better understand employee perspectives on wGT, employees were surveyed at a large biomedical research institution. Survey respondents were presented with three hypothetical scenarios for accessing health-related genomic testing: via (1) their doctor; (2) their workplace; and 3) a commercial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…As anticipated, it proved challenging to gather complete data on U.S. companies offering wGT in the context of voluntary wellness programs, despite employing multiple, complementary data‐collection strategies. While a few studies have focused on wGT, including McDonald et al (2020), Hendricks‐Sturrup et al (2020), and Sanghavi et al (2021), to our knowledge, no prior study has attempted to identify the prevalence and distribution of wGT among U.S. employers. While the often‐cited 2018 SHRM study states that 18% of U.S. employers offer wGT to their employees, there are not methods offered for its analysis.…”
Section: Discussionmentioning
confidence: 99%
“…As anticipated, it proved challenging to gather complete data on U.S. companies offering wGT in the context of voluntary wellness programs, despite employing multiple, complementary data‐collection strategies. While a few studies have focused on wGT, including McDonald et al (2020), Hendricks‐Sturrup et al (2020), and Sanghavi et al (2021), to our knowledge, no prior study has attempted to identify the prevalence and distribution of wGT among U.S. employers. While the often‐cited 2018 SHRM study states that 18% of U.S. employers offer wGT to their employees, there are not methods offered for its analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Some GWPs give employees access to genetic counselors to discuss their reports, while other encourage employees to discuss them with their existing health care providers. [4][5][6][7] In some respects, GWPs appear similar to other types of workforce wellness programs. GWP proponents believe they can contribute toward workforce health promotion, helping to control employer and employee health care costs, and helping employers attract, retain, and engage talented employees who appreciate access to cutting-edge benefits.…”
Section: Purposementioning
confidence: 99%
“…Some GWPs give employees access to genetic counselors to discuss their reports, while other encourage employees to discuss them with their existing health care providers. 4 - 7 …”
Section: Purposementioning
confidence: 99%
“…For example, executives at some US companies offering wGT have described this offering as "creating goodwill" with employees and being "a differentiator" that sets them apart from competing employers 20 . However, we have only limited data in the US or elsewhere on employee perspectives and concerns about wGT that would enable us to evaluate such claims 21 .…”
Section: The Appeal Of Genetic Testing As a Wellness Benefitmentioning
confidence: 99%
“…Of the 594 respondents, 70% of respondents indicated that they would prefer genetic testing in the workplace over a doctor's office or DTC setting, though the survey did not solicit rationale. In addition, over 60% of respondents wanted to know about relevant laws and policies in place to protect their privacy and confidentiality 21 . It is important to note that the participants in this study were employed at a biomedical research institution that specifically focuses on genomics, and their views may not be representative of the broader population of employees' views towards wGT.…”
Section: The Appeal Of Genetic Testing As a Wellness Benefitmentioning
confidence: 99%